2021
DOI: 10.1094/pdis-02-21-0418-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Root Rot Caused by the Fusarium oxysporum Species Complex on Codonopsis pilosula in China

Abstract: Codonopsis pilosula Franch., also known as Dangshen, is an important medicinal plant in China. It is widely cultivated for a major income of local farmers in Dingxi, Gansu Province. Its dried roots have the effects of supplementing vital energy, nourishing spleen and lung, enhancing organic immunity, helping depressurization, and improving microcirculation, etc., for humans. In June to October, 2018-2020, root rot disease was observed on C. pilosula with incidences up to 20% in the Dingxi region. We collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Codonopsis alkyne (lobetyolin) is one of the characteristic components of CP, which has a variety of physiological activities, such as anti-inflammatory, anticancer, and immunomodulatory activities [ 14 ]. Codonopsis alkynes are also one of the active components of CP protecting gastric mucosa [ 15 ]. In addition, CP also includes various sterols and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Codonopsis alkyne (lobetyolin) is one of the characteristic components of CP, which has a variety of physiological activities, such as anti-inflammatory, anticancer, and immunomodulatory activities [ 14 ]. Codonopsis alkynes are also one of the active components of CP protecting gastric mucosa [ 15 ]. In addition, CP also includes various sterols and alkaloids.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that Salvia miltiorrhiza , Angelica sinensis , and Ligusticum chuanxiong improve blood circulation [ 30 32 ]. In addition, Salvia miltiorrhiza and Radix Angelicae sinensis prevent thrombosis [ 33 , 34 ], whereas Salvia miltiorrhiza and Codonopsispilosula improve the microcirculation [ 30 , 35 , 36 ] and regulate immunity [ 37 39 ]. In addition, the tonic recipe also intervenes in the metabolic pathways of the interconversion of pentose and glucuronide, lysine degradation, and histidine metabolism in the body.…”
Section: Discussionmentioning
confidence: 99%
“…A. elegans is widely distributed in soil, feces, grass, and air [7] and thrives under conditions of high temperature, high humidity, and poor ventilation, with the optimal growth and enzyme production environment being at temperatures of 25-30 • C, pH 6-7, and approximately 97% humidity. Similar to other fungi (like Penicillium and Monascus), A. elegans possesses strong decomposition capabilities for protein and fat [8,9]. Currently, the control of post-harvest diseases in fresh C. pilosula primarily relies on chemical agents such as sulfur dioxide fumigation.…”
Section: Introductionmentioning
confidence: 99%